THE EFFECTIVENESS OF ANCHOVY INTAKE ON EPITHELIAL SOCKET THICKNESS POST EXTRACTION - Tecky Indriana; Agus Sumono; Kunti Sholihah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Epithelial formation or re-epithelialization is one of the parameters in the wound closure. Nutrition has become a major factors in the successful outcome during this process. Anchovy (Stolephorus sp.) contains several proteins, vitamins, and minerals that can act as supplements to support wound closure. This research proposed to understand the effect of anchovy intake toward epithelial thickness of the rats post tooth extraction.Method: This research was an experimental laboratory with a post-test-only control group design using 24 rats as a sample. Rats were divided into 2 groups, the control and the treatment group with 12 rats each. The mandibular left first molar of the samples was extracted, then given with aquadest (the control) and anchovy powder (the treatment) during 3, 5, and 7 days. All rats were decapitated after 24 hours from the last treatment, followed by tissue processing and staining with Hematoxylin-Eosin (HE) for examination. A microscope that connects with optilab on a magnification of 100x was used to measure the epithelial thickness on the thickest and thinnest part of the epithelial. The data were analysed with One-way ANOVA test and LSD test. Result: The results showed that the epithelial thickness of the treatment group was significantly increased compared to the control group (p<0.05). Conclusion: This study concludes that the anchovy (Stolephorus sp.) intake affects increasing epithelial socket thickness of the rats post tooth extraction.